PENILAIAN KINERJA UNIT PENGUJIAN BERKALA KENDARAAN BERMOTOR UNTUK USULAN AKREDITASI (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2016)
ABSTRACT The number of motor vehicles quite rapidly, especially in large cities which have impact on the level of traffic congestion in urban areas. Congestion is often found on almost every street, especially at rush hours, the other is due to increased air pollution and traffic accidents. In order to reduce the negative impact on the environment and to maintain the security and safety of motorists, it is necessary to test motor vehicles carefully and carried out by professional staff accordingly. In Law No. 22 Year 2009 regarding Traffic and Road Transportation Article 53 states that regular testing is required to access public transportation, buses cars, freight cars, trailer, and trains operated patch on the road. Periodic testing and inspection activities are including physical testing of motor vehicles, and validation test results. The examination and physical testing of motor vehicles can be carried out by the implementing unit testing regency /municipal government, implementing unit sole agent who received permission from the government, private testing or implementing unit that getting permission from Government. The vehicles which are not roadworthy and do not meet the requirements of the test, should be banned from operating in the street. Vehicles that are not roadworthy may endanger the safety, disruption of traffic on the road and can cause environmental pollution. Therefore, the implementation of periodic test vehicles should be used as one element of a counterforce or